Impact of HIV comprehensive care and treatment on serostatus disclosure among Cameroonian patients in rural district hospitals. - Marie Suzan-Monti; Charles Kouanfack; Sylvie Boyer; Jérôme Blanche; Renée-Cécile Bonono; Eric Delaporte; Patrizia M Carrieri; Jean-Paul Moatti; Christian Laurent; Bruno Spire; Stratall ANRS 12-110/ESTHER Study Group (PLoS ONE)
This work aimed to analyze the rate of disclosure to relatives and friends over time and to identify factors affecting disclosure among seropositive adults initiating antiretroviral therapy (ART) in rural district hospitals in the context of decentralized, integrated HIV care and task-shifting to nurses in Cameroon. Stratall was a 24-month, randomized, open-label trial comparing the effectiveness of clinical monitoring alone with laboratory plus clinical monitoring on treatment outcomes. It enrolled 459 HIV-infected ART-naive adults in 9 rural district hospitals in Cameroon. Participants in both groups were sometimes visited by nurses instead of physicians. Patients with complete data both at enrolment (M0) and at least at one follow-up visit were included in the present analysis. A mixed Poisson regression was used to estimate predictors of the evolution of disclosure index over 24 months (M24).The study population included 385 patients, accounting for 1733 face-to-face interviews at follow-up visits from M0 to M24. The median [IQR] number of categories of relatives and friends to whom patients had disclosed was 2 [1]-[3] and 3 [2]-[5] at M0 and M24 (p-trend<0.001), respectively. After multiple adjustments, factors associated with disclosure to a higher number of categories of relatives and friends were as follows: having revealed one's status to one's main partner, time on ART, HIV diagnosis during hospitalization, knowledge on ART and positive ratio of follow-up nurse-led to physician-led visits measuring task-shifting. ART delivered in the context of decentralized, integrated HIV care including task-shifting was associated with increased HIV serological status disclosure.